Downregulated miR‐144‐3p contributes to progression of lung adenocarcinoma through elevating the expression of EZH2. (2nd October 2018) - Liu, Chao; Yang, Zuozhang; Deng, Zhiyong; Zhou, Youjun; Gong, Quan; Zhao, Ruilian; Chen, Ting
Abstract: Objectives: The intention of our study was to investigate the relationship between miR‐144‐3p and EZH2 as well as the effects of their interaction on cell propagation and invasiveness in lung adenocarcinoma (LUAD). Methods: The expression levels of miR‐144‐3p and EZH2 in LUAD tissues and normal tissues were determined by qRT‐PCR. The dual‐luciferase reporter assay was utilized to validate the targeting relationship between miR‐144‐3p and EZH2 . MTT assay and colony formation assay were performed to evaluate the viability and propagation of LUAD cells, while the effects of miR‐144‐3p and EZH2 on LUAD cell invasiveness were confirmed by transwell assay. Protein expression levels of VEGFA, MMP2, and MMP9 were measured by Western blot. Furthermore, xenograft tumor models were established to verify the effects of miR‐144‐3p on tumor formation and EZH2, VEGFA, MMP2 and MMP9 expressions in vivo. Results: miR‐144‐3P was downregulated in LUAD tissues, and overexpression of miR‐144‐3p inhibited propagation and invasiveness of LUAD cells. EZH2 was a target of miR‐144‐3p and was highly expressed in LUAD cells. Knockdown of EZH2 could suppress the propagation and invasion of LUAD cells. Increased miR‐144‐3p expression exerted an inhibitory effect on LUAD tumor formation in vivo. Conclusion: Overexpression of miR‐144‐3p impeded the propagation and invasiveness of LUAD cells by targeting EZH2 . Abstract : miR‐144‐3p may be one of the candidates for new molecular diagnosis and prognosis in lung adenocarcinoma (LUAD). This study suggested miR‐144‐3p as a potential anticancer agent for therapy of LUAD.